Analisis dan Perancangan Sistem Informasi Penjualan Merry Collection menggunakan Metodologi Ripple - Chenni Irnandha; Djoko Pramono; Buce Trias Hanggara (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Merry Collection is an MSME that offers locally product women's bags. In carrying out its sales activities, Merry Collection uses conventional methods which in practice there are still problems, in getting new customers and complaints from customers which have an impact on reducing sales turnover. Because of this, research for making design recommendation of sales information systems is carried out. The stages involved in making this system design recommendation are modeling and evaluating business processes, analyzing and designing system, and system design evaluation. Evaluation of business processes using QEF shows 12 quality factors that different with the target. The results of requirements analysis and system design using ripple are activity diagrams, class diagrams, use case diagrams, database schemes, sequence diagrams, and interface designs. The evaluation results using the Traceability Matrix and SUS show that all system requirements have been modeled and produce a SUS value of 86 which is equivalent to the value of â€œAâ€. The SUS value indicates that the system design is good and acceptable in terms of usability.